2018
DOI: 10.1186/s40834-018-0076-7
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones modulate multidrug resistance transporters in the ovary

Abstract: BackgroundMultidrug resistance transporters (MDRs) are transmembrane proteins that efflux metabolites and xenobiotics. They are highly conserved in sequence and function in bacteria and eukaryotes and play important roles in cellular homeostasis, as well as in avoidance of antibiotics and cancer therapies. Recent evidence also documents a critical role in reproductive health and in protecting the ovary from environmental toxicant effects. The most well understood MDRs are MDR-1 (P-glycoprotein (P-gp) also know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…P-gp responded strongly to LH and progesterone, indicating that this transporter plays an important role in regulating oocyte formation and steroidogenesis (28). P-gp and BCRP in ovarian endothelial cells can prevent potentially harmful foreign substances (including drugs and environmental toxins) from entering the body, protecting the ovaries from toxins and metabolite accumulation (29). Therefore, we speculated that ABC transporters are highly important for maintaining the microenvironment of the ovary and protecting the ovary from harmful substance accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp responded strongly to LH and progesterone, indicating that this transporter plays an important role in regulating oocyte formation and steroidogenesis (28). P-gp and BCRP in ovarian endothelial cells can prevent potentially harmful foreign substances (including drugs and environmental toxins) from entering the body, protecting the ovaries from toxins and metabolite accumulation (29). Therefore, we speculated that ABC transporters are highly important for maintaining the microenvironment of the ovary and protecting the ovary from harmful substance accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters on the cell membrane could be classified as exporters [42] or importers which rely on the direction of transportation against the cytoplasm [43]. The ABC transporters have been shown to be related to the occurrence of multidrug resistance [44], human diseases such as cancer [45], and inflammatory bowel disease [46]. The abundance of ABC transporters enrichment is increased after treatment with BBA, which might be associated with advance of absorption of nutrients, vitamins, and metabolites [47].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that upon treatment of estrogen, multidrug-resistant ER-α-positive breast cancer cells downregulate P-gp but not ABCB1 RNA [121,122], suggesting a post-transcriptional mechanism of regulation. In an ovarian cancer model, treatment with estrogen also downregulated P-gp protein without amplification of ABCB1; however, they found that treatment with progesterone did increase ABCB1 RNA, and a combination treatment of estrogen and progesterone led to lower ABCB1 RNA and P-gp levels [123]. While conflicting results have arisen regarding estrogen-and ER-α-mediated regulation of ABCB1, it appears that there is a connection worth studying, and outcomes may have important implications in hormone-driven resistant cancers such as breast and ovarian.…”
Section: Transcriptional Regulation Of Abcb1mentioning
confidence: 98%